Abiological catalysis by myoglobin mutant with a genetically incorporated unnatural amino acid. Issue 9 (14th May 2021) - Chand, Subhash; Ray, Sriparna; Yadav, Poonam; Samanta, Susruta; Pierce, Brad S.; Perera, Roshan
Abstract : To inculcate biocatalytic activity in the oxygen-storage protein myoglobin (Mb), a genetically engineered myoglobin mutant H64DOPA (DOPA = L-3, 4-dihydroxyphenylalanine) has been created. Incorporation of unnatural amino acids has already demonstrated their ability to accomplish many non-natural functions in proteins efficiently. Herein, the presence of redox-active DOPA residue in the active site of mutant Mb presumably stabilizes the compound I in the catalytic oxidation process by participating in an additional hydrogen bonding (H-bonding) as compared to the WT Mb. Specifically, a general acid-base catalytic pathway was achieved due to the availability of the hydroxyl moieties of DOPA. The reduction potential values of WT (E° = −260 mV) and mutant Mb (E° = −300 mV), w.r.t. Ag/AgCl reference electrode, in the presence of hydrogen peroxide, indicated an additional H-bonding in the mutant protein, which is responsible for the peroxidase activity of the mutant Mb. We observed that in the presence of 5 mM H2 O2, H64DOPA Mb oxidizes thioanisole and benzaldehyde with a 10 and 54 folds higher rate, respectively, as opposed to WT Mb. Based on spectroscopic, kinetic, and electrochemical studies, we deduce that DOPA residue, when present within the distal pocket of mutant Mb, alone serves the role of His/Arg-pair of peroxidases.